Intestinal Occlusion Secondary to Meckel's Diverticulum: Clinical Case - Ramírez-Vázquez, José Luis; Rosas-Zamora, Alma Jocelyn; Rodríguez-Trejo, Manuel José; Falcón-Cancino, Luis Arturo; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction: The diverticulum results from fibrous obliteration of the umbilical portion of the omphalomesenteric duct, together with the persistence of the ileal portion of the duct, and most of them remain asymptomatic. The diagnosis of Meckel's diverticulum can be a challenge since when it presents symptoms, it does so insidiously and obscures the diagnosis. A high percentage of the complications in adults can be intestinal occlusion. Clinical case: Is presented the clinical case of a 37-year-old male patient with a diagnosis of acute abdomen, initially considered to be of appendicular origin, with subsequent diagnostic rectification at the time of performing a surgical approach, finding a necrotic Meckel's diverticulum, which caused intestinal obstruction, with subsequent confirmation by pathology report. Recovery after surgery was satisfactory. Discussion: Meckel's diverticulum presents the most frequent congenital gastrointestinal malformation and is generally asymptomatic in adults, it can be found as atypical abdominal pain and a fortuitous discovery during surgery for another cause. 1) The rule of two, although ambiguous, can help to suspect and locate the pathology more easily. When Meckel's diverticulum presents clinical manifestations, they are usually non-specific and therefore diagnosis is difficult, even despite studies such as ultrasound or tomography. 2) The presence of symptoms is generally due to the development of complications. Conclusions: Meckel's diverticulum is a congenital anomaly, which occurs in a low proportion of the population, is diagnosed more frequently in men and is usually an incidental finding during the intervention due to lack of suspicion.